The Economic Scale of Small-Medium Enterprises Financing in Sharia Banking - Suhel, Suhel; Asngari, Imam; Mardalena, Mardalena; Andaiyani, Sri (International Journal of Economics and Financial Issues, 2018)
This paper studies factors determining small-medium enterprises (SMEs) financing and calculates economies of scale in sharia banking industry. To that end, we use monthly data from 2012.1 to 2017.6. The methodology used in this paper is multiple linear regression models. The result that showed third-party financing (TPF), labor (L), non-performing financing (TPF) and SMEs financing per branch office (SMEOFCt-1) have had a statistically significant impact on SMEs financing, while the number of branch offices (OFC) hadn’t contributed to SMEs financing. The result of economies scale calculation shows the diminishing return of scale. Some variables like third-party financing (TPF), the number of employees, the number of offices, and NPF shows inelastic. Keywords: Third Party Funds, Non-Performing Financing, SMEs Financing, Economies of scale, Sharia Banking JEL Classifications: G2, G20, L250